The “Bio-Crime Model” of Cross-Border Cooperation Among Veterinary Public Health, Justice, Law Enforcements, and Customs to Tackle the Illegal Animal Trade/Bio-Terrorism and to Prevent the Spread of Zoonotic Diseases Among Human Population - Paolo Zucca; Paolo Zucca; Marie-Christin Rossmann; Marie-Christin Rossmann; Jorge E. Osorio; Kevin Karem; Paola De Benedictis; Josef Haißl; Paola De Franceschi; Elisa Calligaris; Michaela Kohlweiß; Giulio Meddi; et al. (Frontiers in Veterinary Science, 2020)
Illegal animal trade (pet, wildlife, animal products, etc.) is an example of transnational organized crime (T.O.C.) that generates a large business with huge profit margins. This criminal activity causes several negative effects on human health (zoonoses), animal health and welfare, market protection, consumer fraud and may be used as tool of agro/bio-terrorism. Illegal animal trade can facilitate the spread of zoonoses that are defined as diseases and infections that are transmitted by vertebrate animals to man. Humans are affected by more than 1,700 known pathogens: 60% of existing human infectious diseases are zoonotic and at least 75% of emerging infectious diseases of humans have an animal origin and 72% of zoonoses originate from wildlife or exotic animals. The Bio-Crime Project was developed in 2017 by Friuli Venezia Giulia Region (Italy) and Land Carinthia (Austria) together with other public institutions to combat illegal animal trade and to reduce the risk of disease transmission from animals to humans. Project partners agreed that a multi-agency approach was required to tackle the illegal animal trade that was high value, easy to undertake and transnational crime. The Bio-crime model of cross-border cooperation introduces the novel approach of replicating the cooperative framework given by the triad of Veterinary Public Health, Justice and Law Enforcements/Customs across borders using the International Police and Custom Cooperation Centres (IPCCCs) as a connection link among public entities of the neighbor countries. This model has been recognized as a best practice at European level because it can be easily replicated and scaled up without any supplementary cost for Member States.